Against Sexual Violence in the Museum: Art, Curating, and Activism - Perry, Lara; Krasny, Elke (Journal of Cultural Analysis and Social Change, 2022)
Depictions of sexual violence are frequently found in the collections and displays of art museums, and material that represents and affirms violence against women often is displayed unchallenged. This article poses questions about how the presence of this material has been addressed in the relations between feminist activism against sexual violence, art made by artists responding to and participating in feminist activism, and the curatorial activities that have arisen to address the challenges that these activities present to art museums. The chapter investigates the 2021 exhibition Titian: Women, Myth and Power at the Isabella Stewart Gardner Museum and its handling of themes of rape in the central exhibit, Titian’s Rape of Europa; the history of themes of rape in feminist art since the 1970s and in exhibitions of this art that have taken place in museums in the last two decades; and curatorial engagements with sexual violence and rape in recent art exhibitions in the US and in the UK. The article argues that new strategies for the presentation and interpretation of artworks dealing with sexual violence are needed for museums to redress the patriarchal and colonial presence of sexual violence in their collection.
Keywords: Art Curating; Fine Arts; Museum; Museum Violence; Myriam; Rape; Sexual Violence; Visual activism

How Independent Contractors Respond to Sexual Harassment: The Case of the Modeling Industry - Crowley, Jocelyn Elise (Employee Responsibilities and Rights Journal, 2022)
Sexual harassment continues to be a problem that most commonly affects women in the United States workforce today. While there are legal and organizational remedies available, most of these mechanisms for redress only exist for workers in traditional employeremployee contexts. Independent contractors, self-employed workers who represent a growing number of labor force participants in this economy, can therefore only use informal means of addressing sexual harassment. This study used grounded theory methods to analyze 88 separate narratives of sexual harassment from 70 fashion models, an overwhelmingly female set of independent contractors currently operating in the American economy. The aim of the analysis was to understand the mix and meaning behind the use of informal strategies—more specifically confrontation versus non-confrontation—in response to this sexual harassment. Notably, models most often confronted the perpetrators of harassment. Critically, however, those models who chose non-confrontation did not minimize the abuse that they faced. Instead, they either saw themselves as powerless or engaged in self-blame when faced with harassment on the job.
Keywords: Bibliographie; Confrontation; Fashion industry; Independent contractors; Models; Myriam; Nettoyer; Sexual harassment

In Her Own Words: Documenting the Current Realities of Women-in-Jazz - Manfredo, Alexandra, Kiernan Steiner (The Routledge Companion to Jazz and Gender, 2022)
Since the inception of jazz, the lives and experiences of women-in-jazz have been inadequately documented and archived, which has led to a lack of female representation in the jazz community. During the recent resurgence of the #MeToo Movement, many women-in-jazz bravely shared stories of sexual discrimination and harassment. As the jazz community continues to address the gender disparity, women’s stories need to be centered in order to address current realities of women-in-jazz. By documenting the experiences of women-in-jazz in higher education as students, educators and performers, sexual discrimination and harassment must be considered as contributing factors of the gender disparity in jazz.
Num Pages: 14
Keywords: Jazz; Music; Myriam

Music as Labour: Inequalities and Activism in the Past and Present - Abfalter, Dagmar; Reitsamer, Rosa (Taylor & Francis, 2022)
This book brings together research at the intersection of music, cultural industries, management, antiracist politics and gender studies to analyse music as labour, in particular highlighting social inequalities and activism. Providing insights into labour processes and practices, the authors investigate the changing role of manifold actors, institutions and technologies and the corresponding shifts in the valuation and evaluation of music achievements that have shaped the relationship between music, labour, the economy and politics. With research into a variety of geographic regions, chapters shed light on the various ways by which musicians’ work is performed, constructed and managed at different times and show that musicians’ working practices have been marked by precarity, insecurity and short-term contracts long before capitalism invited everybody to ‘be creative’. In doing so, they specifically examine the dynamics in music professions and educational institutions, as well as gatekeepers and mechanisms of inclusion and exclusion. With a specific emphasis on inequalities in the music industries, this book will be essential reading for scholars seeking to understand the collective actions and initiatives that foster participation, inclusion, diversity and fair pay amongst musicians and other workers.
Accepted: 2022-05-18T09:38:24Z
Keywords: Music; Myriam; Personnel and human resources management; bic Book Industry Communication::A The arts::AV Music; bic Book Industry Communication::K Economics; business & management::KJ Business & management::KJM Management & management techniques::KJMV Management of specific areas::KJMV2 Personnel & human resources management; finance

Time for a change: women, work, and gender equality in TV production - Milner, Susan; Gregory, Abigail (Media, Culture & Society, 2022)
This article uses Acker’s concept of inequality regimes to analyze qualitative research findings on work-life balance and gender equality for women in British television production. Female survey respondents, focus group participants, and interviewees spoke of their subjective experience of gendered work practices which disadvantage women as women. These findings build on existing research showing gender disadvantage in the industry, leading to loss of human capital and a narrowing of the range of creative experience. They also show that growing numbers of women are seeking alternative modes of production, at a time of increased awareness of inequality. Such alternatives suggest that change is possible, although it is strongly constrained by organizational logics and subject to continued resistance, in line with Acker’s framework of analysis. Visibility of inequalities is the key to supporting change.
Publisher: SAGE Publications Ltd
Keywords: Myriam; TV; TV production; Television

What else can a crush become: working with arts-methods to address sexual harassment in pre-teen romantic relationship cultures - Huuki, Tuija; Kyrölä, Kata; Pihkala, Suvi (Gender and Education, 2022)
Keywords: Myriam

Re-Cognizing Harassment with the Arts - Babulski, Timothy (Phenomenology & Practice, 2022)
Absent mechanisms of restorative justice, victims of sexual harassment, particularly those within the LGBT+ community that are already frequent targets of relational aggression, are unlikely to either report or reckon with the consequences of inappropriate workplace behaviors and discrimination. Written from the perspective of a masculinized bisexual whose encounter with a pervasive culture of sexual harassment and psychological abuse provoked suicidal ideation, this paper employs the artistic practices of illustration as a means of first re-cognizing and recognizing phenomena, a Ricœurean construct of narrative and a palimpsest of multivocal text and images to evoke the lived experience of harassment and an analytic layer to invoke the phenomenon. By drawing, writing, and thinking through the phenomenon, the marriage of artistic and phenomenological approaches allows both researcher and reader to confront the ‘painful truths’ that otherwise resist easy analysis.
Number: 2
Keywords: LGBTIQ; Myriam; Safe spaces; Teaching arts; Visual arts